True Evil - Greg Iles (UK Hodder & Stoughton, 2007)
The idyllic life of busy Natchez doctor Chris Shepard is turned upside down when undercover FBI agent Alex Morse recruits him for a case involving a local divorce attorney who is suspected of murdering the spouses of his clients.
Keywords: Literature (3GdCOHs; Government investigators -- Fiction; General